General characteristics of the work of judges the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
This article discusses the issues related to labour activity of judges in the Republic of Kazakhstan.Outlines the judiciary and court disputes and Affairs. Are the essential properties of the work of judges.Highlights problematic aspects of the differentiation of labor judges. The characteristic of justice in the Republic of Kazakhstan.
Keywords: legal status; court; judiciary; justice